HLA DR Genome Editing with TALENs in Human iPSCs Produced Immune-Tolerant Dendritic Cells - Yoo-Wook Kwon; Hyo-Suk Ahn; Jin-Woo Lee; Han-Mo Yang; Hyun-Jai Cho; Seok Joong Kim; Shin-Hyae Lee; Heung-Mo Yang; Hyun-Duk Jang; Sung Joo Kim; Hyo-Soo Kim (Stem Cells International)
Although human induced pluripotent stem cells (iPSCs) can serve as a universal cell source for regenerative medicine, the use of iPSCs in clinical applications is limited by prohibitive costs and prolonged generation time. Moreover, allogeneic iPSC transplantation requires preclusion of mismatches between the donor and recipient human leukocyte antigen (HLA). We, therefore, generated universally compatible immune nonresponsive human iPSCs by gene editing. Transcription activator-like effector nucleases (TALENs) were designed for selective elimination of HLA DR expression. The engineered nucleases completely disrupted the expression of HLA DR on human dermal fibroblast cells (HDF) that did not express HLA DR even after stimulation with IFN-γ. Teratomas formed by HLA DR knockout iPSCs did not express HLA DR, and dendritic cells differentiated from HLA DR knockout iPSCs reduced CD4+ T cell activation. These engineered iPSCs might provide a novel translational approach to treat multiple recipients from a limited number of cell donors.